Distinct Changes in Functional Connectivity in Posteromedial Cortex Subregions during the Progress of Alzheimer’s Disease - Wu, Yan; Zhang, Yaqin; Liu, Yong; Liu, Jieqiong; Duan, Yunyun; Wei, Xuehu; Zhuo, Junjie; Li, Kuncheng; Zhang, Xinqin; Yu, Chunshui; Wang, Jiaojian; Jiang, Tianzi (Frontiers in Neuroanatomy, 2016)
Alzheimer’s disease is a progressive neurodegenerative disorder which causes dementia, especially in the elderly. The posteromedial cortex, which consists of several subregions involved in distinct functions, is one of the critical regions associated with the progression and severity of Alzheimer’s disease. However, previous studies always ignored the heterogeneity of the posteromedial cortex and focused on one stage of Alzheimer’s disease. Using resting-state functional magnetic resonance imaging, we studied the respective alterations of each subregion within the posteromedial cortex along the progression of Alzheimer’s disease. Our data set consisted of 21 healthy controls, 18 patients with mild cognitive impairment, 17 patients with mild Alzheimer’s disease, and 18 patients with severe Alzheimer’s disease. We investigated the functional alterations of each subregion within the posteromedial cortex in different stages of Alzheimer’s disease. We found that subregions within the posteromedial cortex have differential vulnerability in Alzheimer’s disease. Disruptions in functional connectivity began in the transition area between the precuneus and the posterior cingulate cortex and then extended to other subregions of the posteromedial cortex. In addition, each of these subregions was associated with distinct alterations in the functional networks that we were able to relate to Alzheimer’s disease. Our research demonstrated functional changes within the posteromedial cortex in the progression of Alzheimer’s disease and may elucidate potential biomarkers for clinical applications.